Evaluation and measurement of patient experience - Sherri LaVela; Andrew Gallan (The Beryl Institute, 2014)
Despite the increasing presence of a variety of measures of patient health care experiences in research and policy, there remains a lack of consensus regarding measurement. The objectives of this paper were to: (1) explore and describe what is known about measures and measurement of patient experience and (2) describe evaluation approaches/methods used to assess patient experience. Patient-experience does not simply reflect clinical outcomes or adherence-driven outcomes; rather it seeks to represent a unique encompassing dimension that is challenging to measure. Several challenges exist when measuring patient experience, in part, because it is a complex, ambiguous concept that lacks a common or ubiquitous definition and also because there are multiple cross-cutting terms (e.g., satisfaction, engagement, perceptions, and preferences) in health care that make conceptual distinction (and therefore measurement) difficult. However, there are many measurement and evaluation approaches that can be used to obtain meaningful insights that can generate actionable strategies and plans. Measuring patient experience can be accomplished using mixed methods, quantitative, or qualitative approaches. The strength of the mixed methods design lies not only in obtaining the "full picture," but in triangulating (i.e., cross-validating) qualitative and quantitative data to see if and where findings converge, and what can be learned about patient experience from each method. Similar to deciding which measures to use, and which approaches to utilize in measurement, the timing of measurement must also fit the need at hand, and make both practical and purposeful sense and be interpreted in light of the timeframe context. Eliciting feedback from patients and engaging them in their care and health care delivery affords an opportunity to highlight and address aspects of the care experience that need improvement, and to monitor performance with regard to meeting patient experience goals in the delivery of care. The use of core patient-reported measures of patient experience as part of systematic measurement and performance monitoring in health care settings would markedly improve measurement of the 'total' patient experience and would heighten our understanding of the patient experience within and across settings. Experience Framework This article is associated with the Policy & Measurement lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Policy%20%26%20Measurement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D" target="_blank">Access other PXJ articles related to this lens. Access other resources related to this lens.